A escultura como experiência estética: Rui Chafes e Alberto Carneiro - Vasconcelos, Maria João Pereira de (2020)
The 20th century artistic panorama was deeply marked by the creation of new plastic languages, where countless artists took new paths, seeking in this way to create discourses and innovative artistic proposals. With Marcel Duchamp, a dialogue on the nature of art began, its ready-made provided a reinvention of the artistic panorama, and created a rupture with all the sculptural tradition until then. His pioneering approach opened the way to new languages and consequently to greater artistic freedom, where sculpture asserts itself as an aesthetic experience and the role of the observer gained more importance in the composition and the relationship with the artistic object. The sculptural practices of Rui Chafes and Alberto Carneiro appear as heirs of this artistic legacy initiated by Duchamp, in this sense, and in the context of the history of art, the artists appear as two singular figures, of great importance in the field of contemporary Portuguese sculpture. This dissertation aims to explore and deepen the different artistic languages of the two sculptors, seeking to understand their approach to sculptural production and, subsequently, the relationship established by it with its viewers. Although formally their works at first impression have no similarities, the two sculptural practices are based on identical principles, seeking to achieve a single objective, to provide a unique aesthetic experience to their observers. Rui Chafes defends that sculpture should be touched with the eyes, in the sense that with his art, he intends to stimulate the emotion but also the intellect of the viewer, provoking a transformation of spiritual dimension. Alberto Carneiro wanted his "involvements" to constitute a deeply sensorial experience, believing that sculpture should be "seen" with the hands, appealing not only to the touch but also to all the senses of those who experienced it. In this way, the sculptures of the two artists assume themselves as potentiating elements of the aesthetic experience, in which the observer occupies a prominent place, and therefore, in the limit it is in the aesthetic experience that the existence and meaning of sculpture is fully accomplished.